2011
DOI: 10.1167/iovs.10-5550
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Macular Thickness in Amblyopic Children with Unilateral High Myopia

Abstract: Amblyopic children with unilateral high myopia tend to have a thicker fovea and thinner inner and outer macula in the amblyopic eye compared to the normal fellow eye. The findings indicate that anatomic changes may be present in the retinas of amblyopic children with unilateral high myopia. Future study is warranted to determine whether the mechanism of the macular changes is due to high myopia, amblyopia, or a combination of the two.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
51
3
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 40 publications
5
51
3
2
Order By: Relevance
“…Pang et al showed that amblyopic children with unilateral high myopia tend to have a thicker fovea in the amblyopic eye than in the normal fellow eye. 12 Huynh et al reported a greater foveal thickness in patients with hyperopic anisometropia amblyopia. 9 However, other studies have yielded inconsistent fi ndings.…”
Section: Discussionmentioning
confidence: 97%
“…Pang et al showed that amblyopic children with unilateral high myopia tend to have a thicker fovea in the amblyopic eye than in the normal fellow eye. 12 Huynh et al reported a greater foveal thickness in patients with hyperopic anisometropia amblyopia. 9 However, other studies have yielded inconsistent fi ndings.…”
Section: Discussionmentioning
confidence: 97%
“…The positive correlation prematurity ,LBW, advanced stages of ROP, need for surgical intervention, and the severity of myopia and strabismus are well established [17] The term myopia of prematurity (MOP) was used to distinguish myopic children who were born prematurely with little or no ROP. It was generally believed though not universally held that premature infants had a greater risk of myopia than did their full-term.…”
Section: High Myopia and Prematurity Or Low Birth Weightmentioning
confidence: 99%
“…[3][4][5] However, prospective studies on treatment of amblopia are very few. Considering the limited studies , there is controversy over refractive correction, treatment outcomes, and whether underlying structural abnormalities are present, [6][7][8][9][10][11][12] and some even question the value of attempting treatment at all. 13 The purpose of our study was to evaluate the response of treatment in different age group in form of visual outcome and to know the success rate of treatment in different types of amblyopia.…”
Section: Introductionmentioning
confidence: 99%